-1/8(z-6)=-3/4(z-1/9)

Simple and best practice solution for -1/8(z-6)=-3/4(z-1/9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -1/8(z-6)=-3/4(z-1/9) equation:


z in (-oo:+oo)

(-1/8)*(z-6) = (-3/4)*(z-(1/9)) // - (-3/4)*(z-(1/9))

(-1/8)*(z-6)-((-3/4)*(z-(1/9))) = 0

(-1/8)*(z-6)+(3/4)*(z-1/9) = 0

3/4*(z-1/9)-1/8*(z-6) = 0

3/4*(z-1/9)-1/8*(z-6) = 0

5/8*z+2/3 = 0

5/8*z+2/3 = 0

5/8*z+2/3 = 0 // - 2/3

5/8*z = -2/3 // : 5/8

z = -2/3/5/8

z = -16/15

z = -16/15

See similar equations:

| -1/2(z+1/9)=-3/8(z+1/2) | | 3+6n=7n-5 | | g(x)=x^2-2x-5 | | 1000+700+6x=800+300+8x | | 117-7x=29x+17 | | 7y+21=5 | | -2w-17=4w+19 | | 2/12+3/4 | | 8(2x+5)=3(x+4)+2 | | 7x-2(5-x)=3+2x+1 | | 5*12+13+3*14+2*15+4*16+17+19+3*20/20 | | 12-8m=2m+2 | | 14-(2q+5)=(-2q)+9 | | -3/4x+5/4=x+3 | | 12x+4/4(x-1)(x+1)=5/4 | | 8x-16=4(2x-4) | | 22=4+3t | | x+30=93 | | -1/4y+5/4=-5/6y+5/3 | | -42=14y | | .2x-3=1 | | -5(9r+10)+5r=10(r+10) | | 2.2x-3=1 | | 3r^2+10r-4=84 | | 9-3(9z+1)=-4(-z-6)-8 | | x^3-19x=-30 | | 15=5/9(f-32) | | -2y+20=-5y+5 | | 300-20x=150+20x | | 3.7+3.25x= | | 11x-31=90 | | 21-1/24(3x)=14-1/24(2x) |

Equations solver categories